Regenerative and protective effects of calcium silicate on senescent fibroblasts induced by high glucose. Issue 3 (3rd February 2020) - Li, Bingmin; Bian, Xiaowei; Hu, Wenzhi; Wang, Xiaoya; Li, Qiankun; Wang, Fangfang; Sun, Mengli; Ma, Kui; Zhang, Cuiping; Chang, Jiang; Fu, Xiaobing
Abstract: Diabetic wounds are a common complication of diabetes and therefore a pressing issue for clinicians. High‐glucose (HG)‐induced fibroblast senescence is mainly responsible for delayed wound healing. Calcium silicate (CS), a kind of bioceramic, is thought to have regenerative properties. The aim of this study was to determine the regenerative and protective effects of CS on senescent fibroblasts induced by HG. Fibroblasts were passaged five times and treated with HG and CS. Compared with the normal glucose (NG) group, the proliferation, migration, and differentiation capacity of HG‐induced fibroblasts significantly decreased ( P < .05). After treatment with CS, the functions of HG‐induced senescent fibroblasts were partly restored ( P < .05). The mechanism of the regenerative and protective effects of CS may be related to the decreased reactive oxygen species generation, improved senescent state (SA‐β‐gal expression decreased), up‐regulated expression of Smad2 and phosphorylated Smad2, and down‐regulated expression of p16, p21, and p53. An in vivo experiment also demonstrated that CS had a therapeutic effect on diabetic wounds via differentiation of fibroblasts into myofibroblasts and enhanced collagen deposition. These results indicate that CS may be a promising candidate for diabetic wound therapy.